The feeding of children from one to five years (London : His Majesty's Stationery Office)
1942-03 1942 1940s 24 pages 12 FISH AND EGG DISHES. 17. Scrambled Eggs. 25 Eggs. 1 quart Milk. 1/4 lb. Margarine. Salt. Method : Melt margarine in strong pan or in a double saucepan. Beat eggs and add milk. Remove pan from heat and stir egg mixture into melted fat. Cook gently over low light until just set — it is important that this mixture should not be overcooked and toughened. Serve on toast. 18. Creamed Eggs. 25 or 50 Eggs — according to ration. White Sauce — (amount to serve with 50 eggs). 5 quarts Milk. Salt. 10 oz. Flour 4 tablesp. Parsley (chopped) 10 oz. Margarine. Method : Boil eggs hard and shell and slice them. Melt fat and stir in flour. Add milk gradually. Bring to boil and cook for 10-15 minutes. Add eggs and parsley. Serve with baked bread. 19. Fish Cakes. 6 lbs. White Fish. 1/2 lb. Margarine. 9 lbs. Potatoes (freshly cooked and mashed). 3/4 pint Milk. 4 tablesp. Parsley (chopped). Method : Boil fish, remove skin and bone and flake with fork. Mix hot mashed potatoes, fish, milk, margarine and parsley. Put into greased tin, mark in squares, bake until brown — 20 minutes. 20. Fish Pie. 6 lbs. Fish. 1-2 pints White Sauce. 9 lbs. Potatoes. 4 tablesp. Parsley (chopped). Seasoning. 4 ozs. Margarine or Dripping. Method : Steam fish — remove skin and bones. Steam potatoes and mash. Mix the fish with sufficient sauce to moisten and add parsley. Turn, into deep tins or dishes. Cover with mashed potato. Spread evenly with a fork and dot with fat. Reheat in a moderate oven for 30—40 minutes. 21. Stewed Fish. 6 lbs. Cod or Hake. 4 oz. Margarine or Dripping. 9 lbs. Potatoes. 1 to 1 1/2 pints White Sauce. Salt. 4 tablesp. Chopped Parsley. Method : Prepare and cook potatoes : mash and season whilst hot. Prepare fish and stew or bake : remove skin and bones. Line tins or dishes with mashed potatoes. Mix the prepared fish with the sauce, seasoning and parsley and spread over the potatoes. Cover with mashed potatoes, dot with fat. Bake in a moderate oven until hot through and brown — about 20 minutes. 22. Sardines on Toast. 50 Sardines. Toast. 1/4 lb. Margarine. Method : Pound sardines well to crush bones thoroughly. Melt margarine add sardines and heat through. Pile on toast. 127/NU/5/5/1/28